COVID-19 VACCINATION DECISION MAKING IN BREASTFEEDING MOTHERS IN THE TANGERANG AREA BANTEN PROVINCE IN 2021 - Dieta Nurrika; Dian Puspitasari Effendi; Indania Indania; Dwi Pantja Wibowo; Ela Susilawati (IAKMI South Tangerang Branch, 2022)
Abstract Background: Breastfeeding mothers have the opportunity to vaccinate, to protect against Covid-19 infection. Sociodemographic factors, health status, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and health motivation are important in making decisions to vaccinate for breastfeeding mothers. Objective: This study aims to determine the association between sociodemographic characteristics, health status, perceptions of Health Belief Model (HBM) on vaccination decisions for breastfeeding mothers in the Tangerang area. Methods: An analytical design with a cross sectional approach and a total sample of 123 respondents were used in this study in the Tangerang area. Results: Except for the level of education of breastfeeding mothers, sociodemographic and health status factors are not associated with the decision making of Covid-19 vaccination. Based on the analysis of HBM perceptions on the perceived severity, perceived benefits, perceived barriers, cues to action and health motivation have a relationship with decision-making about Covid-19 vaccination in breastfeeding mothers. Conclusions: In the HBM perception assessment there is a relationship between perceived severity, perceived benefits, cues to act, and health motivation with Covid-19 vaccination decision making. Likewise with negative perceptions have nothing to do with vaccine decision making, which is a strong predictor of getting the Covid-19 vaccine. Keywords: Covid-19, decision making, health belief model, vaccination